The Common Entrance Examination - Tancoo, Solomon M.
This article provides a brief history of the Common Entrance Examination in Trinidad and Tobago, describes the features of the revised 1964 examination, and assesses the effectiveness of the tests
Keywords: Common Entrance Examination